Iron catalyzed β-C(sp2)–H alkylation of enamides. (2nd September 2021) - Bertho, Sylvain; Maazaoui, Radhouan; Torun, Damla; Dondasse, Ismaël; Abderrahim, Raoudha; Nicolas, Cyril; Gillaizeau, Isabelle
Abstract : An attractive and cheap alternative approach was developed for the β-C(sp 2 )–H (fluoro)alkylation of a range of cyclic and acyclic non-aromatic enamides using either FeCl2 as a catalyst or a stoichiometric amount of nontoxic iron powder. Abstract : An attractive and cheap alternative approach was developed for the β-C(sp 2 )–H (fluoro)alkylation of a range of cyclic and acyclic non-aromatic enamides using either FeCl2 as a catalyst or a stoichiometric amount of nontoxic iron powder. This reaction is regioselective and exhibits broad substrate scope and good functional group tolerance.